Damage Evolution and Failure Mechanism of Segmental Tunnel Lining - Yu, Yang; Wang, Jinchang; Hu, Xinzan (Civil Engineering Journal, 2025)
The prevention and treatment of damage in segmental tunnel lining structures are critical issues in maintaining tunnel integrity. Understanding the damage evolution and failure mechanisms of these structures is essential for their effective management. This study establishes refined numerical models for shield tunnel segmental linings, incorporating critical factors such as localized weakening around hand holes, multi-interface contact behavior, and embedded reinforcement. A total strain crack model is employed to accurately simulate the nonlinear behavior of concrete. The analysis focuses on the compression-bending failure behavior of segmental joints under positive bending moments and investigates the failure mechanisms of segmental linings subjected to surcharge loading. The results show that the deformation of segmental joints under bending moments can be divided into three stages: linear elasticity, elastoplasticity, and failure. The failure mechanism involves the progressive expansion and penetration of cracks in the core pressure-bearing area, leading to increased crack width, yielding of bolts and rebars, and eventual failure. The overall instability failure of segmental tunnel linings is caused by local failures in areas of low stiffness (joints, hand holes), exhibiting progressive failure characteristics. This study presents significant originality and practical value. A refined analytical model of shield tunnel structures is developed to capture the millimeter-scale cracking characteristics of segmental concrete linings. The model enables precise analysis of the mechanical response of shield tunnels under external construction-induced loading.